PEMODELAN REGRESI BERGANDA UNTUK DATA DALAM STUDI KECERDASAN EMOSIONAL - BASRI, HASAN (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2018)
Regression analysis is frequently used to study forecasting and relation between some variables. In studying forecasting and relation between some variables using regression, needed the best model. This research aim to multiple regression modelling for data in emotional intelligence studies and applied to the case for identified of factors influence the student emotional intelligence in Institut Agama Islam Negeri Bone. The research objective was knowledge the best regression linear model and factors influence to the emotional intelligence. The results showed the best regression linear model to knowledge influence factors of the student emotional intelligence in Institut Agama Islam Negeri Bone is, i = 77.6 + 0.468X1i + 0.295X2i + 0.35X3i. Based on this model, imagination, cognition, and personalityis significant influence to the emotional intelligence.